Jitter error evaluation in large-aperture optical telescopes based on normalized point source sensitivity - Yuan-Guo, Liu; Fei, Yang; Jia-Kang, Zhu; Yin-Long, Huo (Frontiers in Astronomy and Space Sciences, 2023)
To comprehensively analyze the jitter error of large aperture optical telescopes, this paper introduces the normalized point source sensitivity (PSSn) to evaluate the telescope system. Firstly, the concept and basic properties of PSSn were introduced, and then the jitter error under expected random loads and the contribution percentage of each mode to the total jitter were analyzed through a model. The PSSn of the system under the influence of different error sources was studied and its variation trend was estimated. By comparing evaluation methods such as Strehl ratio, it reflects the characteristics of more accurate data and concise calculation. The jitter error evaluation method proposed in this article, combined with PSSn, provides practical and beneficial guidance for the design and detection of large aperture optical telescope systems.